From a rise in B to a fall in C? Environmental impact of biofuels - Giuseppe Piroli; Miroslava Rajcaniova; Pavel Ciaian; d'Artis Kancs (Economics and Econometrics Research Institute (EERI), 2014)
This is the first paper that econometrically estimates the impact of the rising Bioenergy production on the global CO2 emissions. We apply a structural vector autoregression (SVAR) approach to time series with annual observation for the world biofuel production and global CO2 emissions from 1961 to 2009. We find that in the medium- to long-run biofuels significantly reduce global CO2 emissions: the CO2 emission elasticities with respect to biofuels range between -0.57 and -0.80. In the short-run, however, biofuels may increase CO2 emissions temporarily (elasticity 0.57). Our findings complement those of life-cycle assessment and simulation models. However, by employing a more holistic approach and obtaining more robust estimates of environmental impact of biofuels, our results are particularly valuable for policy makers.
Keywords: C14; C22; C51; D58; Q11; Q13; Q42; 330; Biofuels; C02 emissions; environmental impact; SVAR